KONTRIBUSI MODAL SOSIAL DALAM PENGEMBANGAN OTOMASI PERPUSTAKAAN: STUDI KASUS KOMUNITAS SLiMS (SENAYAN LIBRARY MANAGEMENT SYSTEM) YOGYAKARTA - Prasetyawan, Yanuar; Krismayanti, Ika (BACA: Jurnal Dokumentasi dan Informasi, 2025)
Today the implementation of information technology in libraries has become a basic need to organize the information, not least in Indonesia. Lack of economic capital (fund) and intellectual capital (human resources that have IT educational background) cause many library in Indonesia can not be able to buy or self develop the information technology. However SLiMS attend like a panacea, which capable of treating and eliminating the limitations of most libraries in Indonesia. SLiMS is an open source software for the Library Management that can be downloaded and implemented for free. In addition Slims rarely have the power owned by a software (information systems) that is a SLiMS User Community. In Indonesia, SLiMS User Community has mushrooming in various regions across Indonesia, one of them in Yogyakarta. Growth and development of SLiMS User Community in Yogyakarta is a manifestation of social capital for the library with lack of information technology implementation. The purpose of this study is to reveal the values and norms are upheld by the Yogyakarta SLiMS User Community that foster social capital which drives community activities as an agent who eliminate the lack of economic capital and intellectual capital that suffered by many libraries in Indonesia. The method used is qualitative method with phenomenological approach. The results showed that the values and norms are upheld together by the Yogyakarta SLiMS User Community is becoming a agent of change of the library conditions in Indonesia, to contribute the automation development in Indonesia. That value and norms are expressed through the sinau bareng. Through sinau bareng, they were learning together to implement SLiMS. Sinau bareng was held each month by a Yogyakarta SLiMS User Community. it became the antidote the lack of libraries. So it will bring justice for all types of libraries to have the right to fulfi ll their basic needs of implementing information technology as library management system.